Courting Failure How Competition for Big Cases Is Corrupting the Bankruptcy Courts - LoPucki, Lynn (University of Michigan Press, 2006)
LoPucki's provocative critique of Chapter 11 is required reading for everyone who cares about bankruptcy reform. This empirical account of large Chapter 11 cases will trigger intense debate both inside the academy and on the floor of Congress. Confronting LoPucki's controversial thesis-that competition between bankruptcy judges is corrupting them-is the most pressing challenge now facing any defender of the status quo."" -Douglas Baird, University of Chicago Law School ""This book is smart, shocking and funny. This story has everything-professional greed, wrecked companies, and embarrassed judges. Insiders are already buzzing."" -Elizabeth Warren, Leo Gottlieb Professor of Law, Harvard Law School ""LoPucki provides a scathing attack on reorganization practice. Courting Failure recounts how lawyers, managers and judges have transformed Chapter 11. It uses empirical data to explore how the interests of the various participants have combined to create a system markedly different from the one envisioned by Congress. LoPucki not only questions the wisdom of these changes but also the free market ideology that supports much of the general regulation of the corporate sector."" -Robert Rasmussen, University of Chicago Law School A sobering chronicle of our broken bankruptcy-court system, Courting Failure exposes yet another American institution corrupted by greed, avarice, and the thirst for power. Lynn LoPucki's eye-opening account of the widespread and systematic decay of America's bankruptcy courts is a blockbuster story that has yet to be reported in the media. LoPucki reveals the profound corruption in the U.S. bankruptcy system and how this breakdown has directly led to the major corporate failures of the last decade, including Enron, MCI, WorldCom, and Global Crossing. LoPucki, one of the nation's leading experts on bankruptcy law, offers a clear and compelling picture of the destructive power of ""forum shopping,"" in which corporations choose courts that offer the most favorable outcome for bankruptcy litigation. The courts, lured by big money and prestige, streamline their requirements and lower their standards to compete for these lucrative cases. The result has been a series of increasingly shoddy reorganizations of major American corporations, proposed by greedy corporate executives and authorized by case-hungry judges.